Gentrification and the Symbolic Marginalisation of Kampung Muara Through the Urban Development Project - Famela, Jely Agri; Naibaho, Rini; Rusdianto, Megawati; Febriani, Kadek Risna; Sitorus, Alhamudin Maju Hamonangan (Jurnal Sosiologi Andalas, 2025)
This article aims to analyse the multidimensional impacts of the gentrification process in Kampung Muara, Teluk Naga, resulting from the mega development project. We used the conceptual framework of Harding and Blokland (2014) to understand displacement as part of gentrification, which is shown as a physical eviction and a gradual process that includes symbolic and social marginalisation and spatial inequality. The Qualitative method was used through in-depth interviews with Kampung Muara's residents. Findings from interviews with affected residents in Kampung Muara indicate that the construction of megaprojects in urban areas has limited local people’s economic and social access due to concrete barriers, caused environmental degradation by construction-related pollution, and reinforced disconnection from the surrounding neighborhoods. The contrast between the fishing village and the spectacular image of a "fantasy city" reinforces symbolic boundaries that delegitimize the existence of the local community. This article argues that gentrification around the affected villages could produce structural inequality through exclusive spatial arrangements and urban imaginaries. These findings enrich studies of gentrification in the Global South and provide a deeper understanding of how gentrification operates through everyday forms of dispossession and symbolic violence.